Pairing Bloom’s Taxonomy Higher-Cognitive Domains and Audience Design to Improve EFL Students’ Responses - Mai Idrees Zaghab; Emad A.S. Abu-Ayyash (Journal of English Language Teaching and Linguistics, 2025)
The study sought to explore the effect of pairing audience design and higher-cognitive domains in teachers’ initiations (I) on generating improved students’ responses (R) in the EFL classroom. To meet this aim, in-depth data were gathered via a qualitative approach utilizing observations and interviews. Ten classes of observation were conducted in an EFL class with 24 students, and semi-structured interviews were held with 7 language teachers. The findings of the study revealed that integrating audience design and higher-cognitive domains into teachers’ initiations generated students’ responses that were effective enough to maintain the flow of conversation, represented in the IRF sequence. This kind of conversational exchange flow secured effective and communicative classrooms. The study highlights the potential for a more student-centered IRF exchange through strategic initiation planning and suggests pedagogical practices aimed at fostering inclusive and interactive classroom environments. The implications of the findings emphasize that improving the communication flow in language classrooms can be achieved by designing interactive tasks that employ audience design and higher cognitive skills.